Continuous Delivery for Mobile with fastlane : Automating mobile application development and deployment for iOS and Android. - Katz, Doron (Packt Publishing, 2018)
Competitive mobile apps depend strongly on the development team's ability to deliver successful releases, with the ability to release consistently and often. Whereas continuous integration has taken on a more mainstream priority amongst the development industry, companies are starting to realize the importance of continuity extends beyond ...